Kinerja Keuangan: Intellectual Capital Performance dan Investment Opportunity Set - Muslih, Muhamad; Aqmalia, Wima Rizky (Jurnal Ilmiah Akuntansi, 2020)
This study aims to examine the factors that affect financial performance, i.e. Intellectual Capital Performance measured using the Extended Value Added Intellectual Capital Plus and Investment Opportunity Set methods measured using investment-based joint proxy. The population used for the object of research is manufacturing sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. Based on the purposive sampling method, a sample of 15 companies was obtained with a study period of 5 years so that the research data amounted to 75 data. By using multiple linear regression analysis techniques, this study proves that the Intellectual Capital Performance and Investment Opportunity Set influences the positive and significant direction of Financial Performance. The results of the study indicate an increase in Intellectual Capital Performance and Investment Opportunity Set will improve the company's financial performance in the aspect of profitability.